Stan cech somatycznych i sprawność ogólna uczniów w wieku 17 lat z centrum kształcenia zawodowego i ustawicznego w Więcborku = Somatic features state and general performance of pupils aged 17 years with centre of vocational training and learning in Wiecbo - Mateusz Szary; Marek Napierała; Małgorzata Pezala; Walery Zukow; Mirosława Cieśłicka; Radosław Muszkieta; Sergii Iermakov; Pavol Bartik; Jerzy Eksterowicz; Robert Stępniak; Vlastimila Karaskova (Kazimierz Wielki University, 2015)
Szary Mateusz, Napierała Marek, Pezala Małgorzata, Zukow Walery, Cieśłicka Mirosława, Muszkieta Radosław, Iermakov Sergii, Bartik Pavol, Eksterowicz Jerzy, Stępniak Robert, Karaskova Vlastimila. Stan cech somatycznych i sprawność ogólna uczniów w wieku 17 lat z centrum kształcenia zawodowego i ustawicznego w Więcborku = Somatic features state and general performance of pupils aged 17 years with centre of vocational training and learning in Wiecbork. Journal of Education, Health and Sport. 2015;5(5):300-311. ISSN 2391-8306. DOI 10.5281/zenodo.17787 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A300-311 https://pbn.nauka.gov.pl/works/560812 http://dx.doi.org/10.5281/zenodo.17787 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015.   STAN CECH SOMATYCZNYCH I SPRAWNOŚĆ OGÓLNA UCZNIÓW W WIEKU 17 LAT Z CENTRUM KSZTAŁCENIA ZAWODOWEGO I USTAWICZNEGO W WIĘCBORKU   SOMATIC FEATURES STATE AND GENERAL PERFORMANCE OF PUPILS AGED 17 YEARS WITH CENTRE OF VOCATIONAL TRAINING AND LEARNING IN WIECBORK   Mateusz Szary1, Marek Napierała2, Małgorzata Pezala2, Walery Zukow2, Mirosława Cieśłicka2, Radosław Muszkieta2, Sergii Iermakov2, Pavol Bartik2, Jerzy Eksterowicz2, Robert Stępniak2, Vlastimila Karaskova2  1Wyższa Szkoła Gospodarki w Bydgoszczy 2Uniwersytet Kazimierza Wielkiego w Bydgoszczy   Key words: physique, overall efficiency students.   Słowa kluczowe: budowa ciała, sprawność ogólna uczniów.   Abstract The aim of the study was to evaluate somatic and motor skills, pupils from the first Centre for Continuing Education and Training in Wiecbork. The study included 29 girls and 29 boys. The measurements were carried out in the spring of 2014. Assessment of somatic was determined based on height and weight. All research results are presented by means of tables and figures. To assess the level of selected motor skills benefited from the International Physical Fitness Test. Conclusions: 1. Among the surveyed boys and girls prevails leptosomatic type. 2. Respondents both boys and girls disappear overall fitness peers from regional and national studies.   Streszczenie Celem badań była ocena cech somatycznych oraz zdolności motorycznej uczniów z klas pierwszych Centrum Kształcenia Ustawicznego i Zawodowego w Więcborku. Badaniem objęto 29 dziewcząt i 29 chłopców. Pomiary przeprowadzono wiosną 2014 roku. Ocena stanu somatycznego została określona na podstawie wysokości i masy ciała. Wszystkie wyniki badań zostały przedstawione za pomocą tabel i rycin. Do oceny poziomu wybranych zdolności motorycznych skorzystano z Międzynarodowego Testu Sprawności Fizycznej. Wnioski: • Wśród badanych chłopców i dziewcząt przeważa typ leptosomatyczny. • Badani zarówno chłopcy jak i dziewczęta ustępują w sprawności ogólnej rówieśnikom z badań regionalnych i ogólnopolskich.